2020
DOI: 10.1523/jneurosci.1553-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Inhibition Imbalance Leads to Alteration of Neuronal Coherence and Neurovascular Coupling under Acute Stress

Abstract: Planning & Evaluation (IITP) grant funded by the Korea government (MSIT) (No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Moreover, the PSD analysis provided novel insights into the physiology where a significantly lower relative power in 0.021-0.052 Hz (smooth muscle autonomic innervation) frequency band in elderly subjects with T2DM during the Mini-Cog three-item recall test potentially due to small fiber neuropathy [13] in the pial vessels. Furthermore, a drop in the oscillatory power in the 0.01-0.02-Hz frequency band during Mini-Cog three-item recall test due to cognitive load likely under acute stress [18], where the drop was more pronounced in the elderly subjects with T2DM, possibly because of glucocorticoid receptor signaling in T2DM [19]. Notably, transcranial electrical stimulation induces brain energy consumption that promotes systemic glucose uptake [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PSD analysis provided novel insights into the physiology where a significantly lower relative power in 0.021-0.052 Hz (smooth muscle autonomic innervation) frequency band in elderly subjects with T2DM during the Mini-Cog three-item recall test potentially due to small fiber neuropathy [13] in the pial vessels. Furthermore, a drop in the oscillatory power in the 0.01-0.02-Hz frequency band during Mini-Cog three-item recall test due to cognitive load likely under acute stress [18], where the drop was more pronounced in the elderly subjects with T2DM, possibly because of glucocorticoid receptor signaling in T2DM [19]. Notably, transcranial electrical stimulation induces brain energy consumption that promotes systemic glucose uptake [20].…”
Section: Discussionmentioning
confidence: 99%
“…Its activity reflects the influences of neurotransmitters and other vasoactive mediators on each of these cell types as well as metabolic demand ( 51 , 52 ). In a mouse model, Han et al ( 53 ) demonstrated that stress could disrupt the neuronal excitatory-inhibitory relationship changing the relationship between neuronal activity and the associated vascular response (neurovascular coupling). While STN-DBS might affect neurovascular coupling on a global or multi-regional basis during speech, neuronal coupling between blood flow and metabolism has been shown to be affected by levodopa, especially in individuals with levodopa induced dyskinesia, but not STN-DBS during the rest state ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, capillary flow was recently suggested not to be a passive consequence of the flow in upstream smooth muscle-unsheathed arterioles, but vice versa; capillary dilation may be a primary event preceding arteriole dilatation ( Kisler et al, 2017 ). In this scenario, capillary dilation would occur as a result of the relaxation of pericytes, and this local dilation would spread from capillaries toward larger arterioles in a secondary step ( Hall et al, 2014 ; Lendahl et al, 2019 ; Han et al, 2020 ). A crucial role of pericytes for capillary vasodilation during hemodynamic responses has been shown in numerous previous studies ( Lourenco et al, 2014 ; Sweeney-Reed et al, 2016 ; Caporarello et al, 2019 ; Alarcon-Martinez et al, 2020 ), although others failed to demonstrate this ( Fernandez-Klett et al, 2010 ; Hill et al, 2015 ; Wei et al, 2016 ; Cudmore et al, 2017 ; Iadecola, 2017 ).…”
Section: Coupling Of Inhibitory/excitatory Circuit Activation To Cerebral Blood Flowmentioning
confidence: 99%
“…On the other hand, pericytes have been shown to express NO-responsive enzymes ( Friebe et al, 2018 ). Also, a pericyte-induced role for vasodilation through capillaries would become feasible, since the large surface area of capillaries and minimal changes in their diameter would produce a large change in blood flow ( Han et al, 2020 ).…”
Section: Coupling Of Inhibitory/excitatory Circuit Activation To Cerebral Blood Flowmentioning
confidence: 99%